Dynamic Analysis of Loneliness at Older Ages in Europe by Gender - Pagán-Rodríguez, Ricardo Braulio; Malo, Miguel Ángel (My University, 2024)
In this article, we analyse loneliness trajectories for older people aged 50 or more in selected European countries by gender. We also focus on the relationship between disability and loneliness trajectories. We use three waves of the longitudinal SHARE database. Loneliness trajectories are non-linear, increasing with age for both genders, and have the same shape irrespective of disability status but with different levels of loneliness. Loneliness persistence increases with disability and disability severity, especially for women. Worsening (improving) disability increases (decreases) the risk of loneliness persistence. We build rankings of the country’s effects on loneliness persistence by gender. Mediterranean and Eastern European countries have the highest persistence rates, while the lowest rates are in Northern countries.
Keywords: Vejez; Soledad; Loneliness persistence; Disability dynamics; Ageing; Cross-national comparison